Graphene-based reconfigurable FSS for dynamic millimeterwave OAM beam generation - Qasem, Nidal (Institute of Advanced Engineering and Science, 2025)
This research paper explores the dynamic generation of orbital angular momentum (OAM) beams at millimeter-wave (mm-wave) frequencies using intelligent reconfigurable metasurfaces (IRM). The ability to dynamically control OAM properties is crucial for unlocking these beams’ full potential. This paper proposes a novel method utilizing a frequency-selective surface (FSS) integrated with reconfigurable graphene to generate an IRM. By carefully designing the FSS elements and controlling the graphene’s electrical conductivity, the system can generate and manipulate mm-wave OAM beams with different topological charges. With the suggested IRM structure, a conversion efficiency of nearly 80% can be achieved in converting the circularly polarized incident wave into its cross-polarized component at 30.7 GHz, with an overall thickness of 0.067 λ. This research has significant implications for advancing mm-wave communications by providing additional spatial dimensions for multiplexing and enhancing system capacity.